The Influence of Sociodemographic Factors on Food Waste Creation - Raisa Maharani; Maswadi Maswadi; Dewi Kurniati (Journal La Lifesci, 2026)
Food waste has emerged as a global issue of growing international concern, with developing countries striving to identify effective strategies to address the problem of food-related waste. In this study, food waste refers specifically to edible household food residues that are discarded despite being fit for consumption. This research aims to analyze the generation of food waste in Singkawang City and to examine the relationship between sociodemographic factors and the amount of food waste generated. The household sampling technique employed in this study was proportionate stratified random sampling, while the selection of individual family member respondents within each household was conducted using incidental sampling. The analytical methods applied include descriptive analysis, food waste quantification, and multiple linear regression analysis. The findings indicate that the highest level of food waste generation occurred in Singkawang Tengah District, producing the largest volume of waste (28,370 kg/year), while the lowest generation was recorded in Singkawang Utara District (7,140 kg/year). Furthermore, the results of the analysis examining the relationship between sociodemographic factors and food waste generation demonstrate that, simultaneously, sociodemographic variables (age, gender, income, education level, occupation, and number of household members) significantly influence the dependent variable (food waste generation). Partially, however, age, gender, education level, and occupation were found not to have a significant effect on food waste generation.